Effect of inulin with different degrees of polymerization on dough rheology, gelatinization, texture and protein composition properties of extruded flour products. (1st April 2022) - Liu, Yixuan; Leng, Yue; Xiao, Shensheng; Zhang, Yudong; Ding, Wenping; Ding, Beibei; Wu, Yan; Wang, Xuedong; Fu, Yang
Abstract: The quality deterioration of extruded flour products has caused serious food waste with huge economic losses. To ameliorate the status, the effect of inulin with different degrees of polymerization on rheology, gelatinization properties of dough, and textural and protein composition properties of extruded flour products was investigated. When short-chain inulin (FS) and long-chain inulin (FXL) were incorporated, the empirical rheological properties of the dough were significantly improved. Besides, the storage and loss modulus of dough dynamic rheology with the incorporation of 8 g/100 g FS or FXL increased to the maximum value and exhibited the best gelatinization characteristics. Textural analysis showed that 4 g/100 g FS and 2 g/100 g FXL extruded flour products yielded minimum hardness and maximum elasticity, with increased moisture content. According to the secondary structure and SDS-PAGE measurement, the protein polymerization increased after inulin addition, which enhanced the strength of gluten. Principal component analysis also showed that there was significant effect of FS and FXL on the dough and extruded flour products. The results obtained can be used to better understand the functionality and food applications of inulin with different degrees of polymerization. Highlights: Inulin incorporation significantly improved the dough rheological properties. 4% FS and 2% FXL exhibited the best quality of extruded flour products. FS and FXL promoted the aggregation and formation of gluten network.